Exploring the relationship between financial literacy and risk-taking propensity in Spanish undergraduates - López-Subires, María Deseada; Molina-García, Jorge Antonio; Cisneros-Ruiz, Ana José; Diéguez-Soto, Julio (My University, 2022)
Financial literacy has aroused significant academic, professional, and institutional interest due to the increasingly complex financial environment in which individual decisions involve greater risk than in the past. However, previous evidence is contradictory about the influence that financial literacy exerts on an individual’s risk-taking propensity, possibly motivated by two fundamental reasons: (1) they incompletely measure financial literacy only through financial knowledge (i.e., evidence shows that financial literacy is a multidimensional construct composed of financial knowledge, attitude, and behaviour); (2) they analyse individuals that are very diverse in terms of their composition, ignoring the heterogeneity that exists in society and making it difficult to obtain consistent conclusions for the different population segments. Therefore, this article applies covariance-based structural equation models to a sample of 568 university students from three different Spanish universities to test the impact of financial literacy, considered multidimensional, on undergraduates’ risk-taking propensity. Our results show that: (1) financial knowledge directly and positively influences risk-taking propensity; (2) financial behaviour directly and positively influences risk-taking propensity; (3) financial attitude indirectly and positively influences risk-taking propensity through financial behaviour. These findings are relevant for both researchers and education policymakers since they evidence the mechanism that explains the relationship between financial literacy and undergraduates’ risk-taking propensity.
Keywords: Educación - Finanzas; Estudiantes universitarios; Financial literacy; Financial knowledge; Financial behaviour; Financial attitude; Risk-taking propensity; Undergraduates